Audit of Rapid Tranquillisation Prescribing and Monitoring Practices at Rohallion Medium and Low Secure Forensic Psychiatry Unit, Murray Royal Hospital, NHS Tayside - Aditya Unni; Oana Maior; Jonathan Bate (BJPsych Open, 2025)
Aims: To assess whether current prescribing and monitoring practices for oral 'as required’ medications and Rapid Tranquillisation align with local and national guidelines.